The effects of empagliflozin on arterial stiffness, endothelial function and ventriculoarterial coupling in type 2 diabetes mellitus: 1 year follow up. (25th November 2020) - Ikonomidis, I; Thymis, J; Pavlidis, G; Birba, D; Kalogeris, A; Kousathana, F; Kostelli, G; Triantafyllou, C; Katogiannis, K; Lampadiari, V; Iliodromitis, E.K
Abstract: Introduction: Sodium glucose cotransporters inhibitors (SGLT2i) are currently used in the treatment of patients with type 2 diabetes mellitus (T2DM) who pose high cardiovascular risk. However their effects on arterial stiffness, endothelial function and ventriculoarterial coupling have not been described. Methods: We recruited 120 patients with T2DM. They received either the SGLT2i empagliflozin (n=60) or insulin (n=60). We measured at baseline and after 1 year of treatment: 1) Perfused Boundary Region (PBR 5–25μm) to evaluate endothelial glycocalyx integrity via Glycocheck, 2) Pulse wave Velocity (PWVc-f), 3)central systolic blood pressure (cSBP), 4) central Pulse Pressure (cPP) via Complior, 5) the ratio PWV/GLS by echocardiography to assess ventriculoarterial coupling (VA coupling). Results: The patients were matched for age, gender, smoking, hypertension and hyperlipidemia (p=NS). Hemoglobin A1c was deteriorated in both groups (8.1% vs 8.2%, p=NS). The baseline measurements of aforementioned markers did not differ between the 2 groups (p=NS). PWV was correlated with cSBP (r=0.4.p<0.05) and cPP (r=0.35, p<0.05) for all participants at baseline. After 1 year of treatment both groups achieved significant reduction of HbA1c. Patients treated with insulin showed an increase of PWV in contrary with empagliflogin group (11.4±0.5 to 12.6±0.4 vs 11.7±0.5 to 10.9±0.4, correspondingly, p<0.05). cSBP declined considerably in empagliflozin group (135±10 to 129±10 vs 134±9 to 136±9 respectively, p<0.05) and cPP remained approximately steady (47±8 to 48±8 vs 49±6 to 55±6 respectively, p<0.05) compared with insulin group. PBR dropped in SGLT2i group (2.20±0.2 to 1.98±0.2, p<0.05) whereas PBR fluctuated at the same level in insulin group (2.18±0.2 to 2.15±0.3, p=NS).PWV/GLS fell in both groups but the reduction was more prominent in empagliflozin group (−0.72±0.1 to −0.67±0.1 vs −0.72±0.1 to −0.60±0.1 respectively, p<0.05). Conclusion: 1 year treatment with empagliflozin resulted in improved markers of arterial stiffness, ventriculoarterial coupling and endothelial function, independently of glycemic control. Funding Acknowledgement: Type of funding source: None